Genome wide identification of the NPR1 gene family in plant defense mechanisms against biotic stress in chili (Capsicum annuum L.) - Ishfaqe, Qandeel; Sami, Adnan; Zeshan Haider, Muhammad; Ahmad, Arsalan; Shafiq, Muhammad; Ali, Qurban; Batool, Alia; Haider, Muhammad Saleem; Ali, Daoud; Alarifi, Saud; Islam, Md Samiul; Manzoor, Muhammad Aamir (Frontiers in Microbiology, 2024)
Chili pepper cultivation in the Indian subcontinent is severely affected by viral diseases, prompting the need for environmentally friendly disease control methods. To achieve this, it is essential to understand the molecular mechanisms of viral resistance in chili pepper. The NONEXPRESSOR OF PATHOGENESIS-RELATED GENES 1 (NPR1) genes are known to provide broad-spectrum resistance to various phytopathogens by activating systemic acquired resistance (SAR). An in-depth understanding of NPR1 gene expression during begomovirus infection and its correlation with different biochemical and physiological parameters is crucial for enhancing resistance against begomoviruses in chili pepper. Nevertheless, limited information on chili CaNPR genes and their role in biotic stress constrains their potential in breeding for biotic stress resistance. By employing bioinformatics for genome mining, we identify 5 CaNPR genes in chili. The promoter regions of 1500 bp of CaNPR genes contained cis-elements associated with biotic stress responses, signifying their involvement in biotic stress responses. Furthermore, these gene promoters harbored components linked to light, development, and hormone responsiveness, suggesting their roles in plant hormone responses and development. MicroRNAs played a vital role in regulating these five CaNPR genes, highlighting their significance in the regulation of chili genes. Inoculation with the begomovirus "cotton leaf curl Khokhran virus (CLCuKV)" had a detrimental effect on chili plant growth, resulting in stunted development, fibrous roots, and evident virus symptoms. . The qRT-PCR analysis of two local chili varieties inoculated with CLCuKV, one resistant (V1) and the other susceptible (V2) to begomoviruses, indicated that CaNPR1 likely provides extended resistance and plays a role in chili plant defense mechanisms, while the remaining genes are activated during the early stages of infection. These findings shed light on the function of chili's CaNPR in biotic stress responses and identify potential genes for biotic stress-resistant breeding. However, further research, including gene cloning and functional analysis, is needed to confirm the role of these genes in various physiological and biological processes. This in-silico analysis enhances our genome-wide understanding of how chili CaNPR genes respond during begomovirus infection.